The reality of the implementation of strategic management among the principals of the schools of the Education Bureau in Al Rawabi In Riyadh - Altwaijri, Fawaz bin Abdullah (Journal of Educational and Psychological Sciences, 2017)
The aim of the study was to identify the degree of ownership and practice of the principals of the schools of the Education Office in Rawabi in Riyadh for strategic management styles from the point of view of the members of the study society. The study was based on the analytical descriptive approach. The study used the questionnaire tool, where the sample of the study consisted of 50 managers in the office of education in Al Rawabi in Riyadh city. The results of the study showed that the principals of the schools of the Education Office in Al-Rawabi in Riyadh had moderate management styles. The general arithmetic mean of this aspect was 3.22. The most prominent of these patterns was the most encouraging of the school staff to benefit from the new educational opportunities available to them. Flexibly with the school staff in accordance with the principle of mutual respect). The results showed that they possessed the skills of strategic management to a medium degree. The general arithmetic average of this aspect was 3.23. The most prominent of these skills were (determining the sources of financial resources supporting the implementation of the school plan and selecting the leadership skills to implement the school plan). Regarding the axis of obstacles to strategic management, the results showed that there were moderate obstacles. The general arithmetic average of this aspect was 3.23. The main obstacles were the imbalance of educational activity within the school due to vacations, transportation, scarcity, absence and delay from morning work, And the Ministry of Education).